Optical Magnetometry Based on Nanodiamonds with Nitrogen-Vacancy Color Centers - Wojciechowski, Adam M. (Materials (Basel), 2019)
Nitrogen-vacancy color centers in diamond are a very promising medium for many sensing applications such as magnetometry and thermometry. In this work, we study nanodiamonds deposited from a suspension onto glass substrates. Fluorescence and optically detected magnetic resonance spectra recorded with the dried-out nanodiamond ensembles are presented and a suitable scheme for tracking the magnetic-field value using a continuous poly-crystalline spectrum is introduced. Lastly, we demonstrate a remote-sensing capability of the high-numerical-aperture imaging fiber bundle with nanodiamonds deposited on its end facet.